KECERDASAN EMOSIONAL DALAM PEMBELAJARAN MATEMATIKA - Adinda, Anita (IAIN PADANGSIDIMPUAN, 2016)
Intelligence is the ability to act by a specific purpose, to think rationally, and to face the surrounding environment effectively. Factors that affect success of learning in affected by emotional intelligence. Learners who have high academic intelligence , they tend to have anxiety is unwarranted, overly critical, fussy, tend to withdraw, seemed cold and less likely to express frustration and anger appropriately. If supported by the low level of emotional intelligence, the leaner is often a source ofÂ problems. When learners have a high IQ but low emotional intelligence level, it tends to be seen as learners stubborn, difficult to get along, easily frustrated, do not easily trust others, not sensitive to environmental conditions and tends to despair when experiencing stress. But the opposite condition experience by learners who have an average IQ level has a high emotional intelligence.